KINERJA DINAS BUDPARPORA KABUPATEN LIMA PULUH KOTA DALAM UPAYA PENGEMBANGAN OBJEK WISATA KAPALO BANDA DI KECAMATAN HARAU - Fajri, Khairil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The development of nature tourism or tourism object of Kepalo Banda by Budparpora Office of Kabupaten Lima Puluh Kota is carried out through planned activities, ie tourism tourism development activities, tourism destination development (improvement and maintenance of tourism facilities and infrastructure), and partnership development through local community role so as to increase tourist visits. However, the development effort of Kepalo Banda tourism object has not been run as planned work plan, where the achievement of tourist visit has decreased by 2015 compared to the previous year.This study uses a qualitative approach with descriptive method in describing the results of research. The research instrument used refers to the theory of organizational performance proposed by Moeheriono that the performance is the achievement of the implementation of activities that poured through strategic planning (Renstra) of an organization. Data collection techniques include, interviews, observation and documentation studies.The results of research performance of Budparpora Service Office of Lima Puluh Kota Regency in the effort of development of Kepalo Banda tourism object in Harau sub district has not run optimally, where not yet the advancement of information and communication technology (ICT) in marketing and promotion development and not yet supported by the availability of facilities and infrastructure in the development of tourist sites, such as maps of the area, boats, and water tourism facilities or river cruises. In addition, the partnership development activities are carried out through the management of tourist objects by villages, but not yet accompanied by training or empowerment to the community in the management of tourist objects, where there is no companion of tourists (guide), and information service location of natural attractions.Keywords: Performance, Tourism Development, Travel Destinations, Traveler